Legitimacy and the Cost of Government - Niclas Berggren; Christian Bjørnskov; David Lipka (Research Institute of Industrial Economics (IFN), 2014)
While previous research documents a negative relationship between government size and economic growth, suggesting an economic cost of big government, a given government size generally affects growth differently in different countries. As a possible explanation of this differential effect, we explore whether perceived government legitimacy (measured by satisfaction with the way democracy works) influences how a certain government size affects growth. On the positive side, a legitimate government may get away with being big since legitimacy can affect people's behavioral response to, and therefore the economic growth cost of, taxation and government expenditures. On the negative side, legitimacy may make voters less prone to acquire information, which in turn facilitates interest-group oriented or populist policies that harm growth. A panel-data analysis of up to 30 developed countries, in which two different measures of the size of government are interacted with government legitimacy, reveals that legitimacy exacerbates a negative growth effect of government size in the long run. This could be interpreted as governments taking advantage of legitimacy in order to secure short-term support at a long-term cost to the economy.
Keywords: E62; H11; H20; O43; Z13; 330; Legitimacy; Economic growth; Size of government; Confidence; Trust